"School reform is like cleaning out your garage": a case study of one school district's influence on student achievement - Gifford, Brenda K., author; Cooner, Donna, advisor; Lucero, Rodrick, advisor (Colorado State University. Libraries, 2009)
The purpose of this qualitative constructivist case study is to explore one school district's organizational constructs, policies, and structures that influence student achievement especially for marginalized students. The focus is on the school district as the unit of analysis. Michael Fullan's (2004) conceptual framework of ten integrated components to realize large-scale systemic improvement in school districts provided a scaffold for the literature review and data analysis. Topical questions included: (1) How do the district's organizational constructs, policies, and structures provide support to schools? (2) How do the theories about school improvement held by the school district leadership team impact the support to schools? 'What is tight' and 'what is loose'? (3) How do the explicit theories of action of the district leadership team materialize into organizational constructs, policies, and structures that impact teaching and learning at the school and classroom level? A small urban school district in Colorado was the focus of this case study. Four themes resulted from direct observations, document reviews, and responsive interviews with district administrators, principals, and teachers. (1) There is a resounding coherence of a collective moral purpose and compelling conceptualization regarding the theory of action and 'what is tight' and 'what is loose' (DuFour, 2007). (2) The alignment and interconnectedness of the organizational constructs and structures with the compelling conceptualization provides a framework of support to schools. (3) Building capacity is a core function throughout the district. (4) There is an emerging understanding of the 'defined autonomy' between the district expectations and each school's unique flexibility. The thread that is woven throughout this dissertation is the interconnectivity between district structures and schools; between hopes and dreams and constructs; and between each one of us, our experiences and the children for whom we advocate. The four themes are a springboard for a call to action to public school advocates to be courageous, to be reflective, be nimble and responsive, create coherence and interconnectedness across school district systems, define autonomy, and be inclusive in all processes.
School reform is like cleaning out your garage: a case study of one school district's influence on student achievement.
Keywords: achievement; case study; coherence; educational structures; increase student achievement; reform; school district; school district reform; school district support to schools; school administration; curriculum development; education philosophy; case studies; academic achievement; students; educational administration; educational philosophy